Sexually Transmitted Infections and Associated Risk Factors Among Male Clients of Sex Workers: A Cross-Sectional Pilot Project in Antwerp, Belgium - Platteau, Tom; De Baetselier, Irith; Van Mieghem, Heleen; Tsoumanis, Achilleas; Keersmaekers, Kris; Ooms, Lieselot; Cuylaerts, Vicky; Florence, Eric (Frontiers in Reproductive Health, 2022)
Introduction Prevalence of sexually transmitted infections (STIs) is increasing in Belgium in recent years. Clients of sex workers form a key population for acquisition of STIs, due to their sexual relations, with or without a condom, with sex workers. STI testing uptake is low among clients of sex workers, and prevalence of STIs remains to be investigated in Belgium. Therefore, we offered STI-testing to clients of sex workers during outreach sessions in Antwerp. Methods Time location sampling (TLS) was used to improve representativeness of the sample during ten test sessions in the red light district, Antwerp in May and September 2019 by using a passive approach. Individuals that were interested to get tested for STIs could enter the study. Participants completed an online survey and samples for STI testing were collected. Testing included HIV, syphilis, Chlamydia trachomatis (Ct) and Neisseria gonorrhoeae (Ng). Test results were communicated via a cell phone message (for negative test results) or by phone (for positive test results). Results In total, 154 male clients of sex workers with a median age of 38 participated. A total of eight Ct and one Ng infections were detected. TLS analysis revealed a Ct/Ng prevalence of 8.2%. No new HIV nor syphilis infections were detected. Using univariate analysis, testing positive for STI was associated with younger age and anorectal sex with a sex worker. Using multivariate analysis, an STI-positive test result was associated with being younger, having non-Belgian nationality, and being in a relationship. Conclusion Our study found a substantial prevalence of Ct/Ng which highlights the need for sensitization and facilitation of STI testing among clients of sex workers. It is difficult to compare results due to the lack of reference material. Moreover, our relatively small convenience sample limits generalizability of results. However, phone counseling (for positive test results) was accepted, linkage to care was provided, and partner notification was facilitated.